Peran Dharmaduta dalam Upaya Membentuk Perilaku Keberagamaan Umat Buddha melalui Metode Pembiasaan - Sukarti Sukarti (STABN Sriwijaya, 2019)
The low belief of Buddhists can be seen from the indicators of religious behavior. Indicators of religious behavior appear in the activities carried out by people both in the temple and at home. The purpose of coaching in the context of Buddhist education is to improve the quality of saddha (faith) and devotion to Buddhists in various aspects of life. This study aims to describe the role of Dharmaduta in shaping religious behavior in fostering people through the habituation method. This research is a qualitative research with descriptive method. The research was carried out in the Madiun Residency area, on the grounds that there were Buddhists and Buddhist formation by Dharmaduta. Data is collected through observation, interviews and documentation. The test for the validity of the data uses triangulation techniques and data source methods. A dharmaduta is an intelligent servant in Buddhism, which means providing services to the people based on their competence and intellect. Religious behavior that is formed in Buddhists is a reflection of the implementation of Buddhist teachings. Habits that are formed will have an effect on increasing Buddhist faith and morality. The religious behavior of Buddhists refers to the ten ways of doing good (dasa puññakiriyavatthu). Habit on behavior that arises based on role models, and special experiences of leaders who in this case are dharmaduta. Rendahnya keyakinan umat Buddha dapat ketahui dari indikator perilaku keberagamaan. Indikator perilaku keberagamaan tampak pada kegiatan yang dilakukan umat baik di vihara maupun di rumah. Tujuan pembinaan dalam konteks penyuluhan agama Buddha adalah meningkatkan kualitas saddha (keyakinan) dan bakti umat Buddha dalam berbagai segi kehidupan. Penelitian ini bertujuan untuk mendeskripsikan peran Dharmaduta dalam membentuk perilaku keberagamaan pada pembinaan umat melalui metode pembiasaan. Penelitian ini merupakan penelitian kualitatif dengan metode deskriptif. Penelitian dilaksanakan di wilayah Karesidenan Madiun, dengan alasan, terdapat umat Buddha dan pembinaan umat Buddha oleh Dharmaduta. Data dikumpulkan melalui observasi, wawancara dan dokumentasi. Uji keabsahan data menggunakan teknik triangulasi metode dan sumber data. Seorang dharmaduta merupakan pelayan yang intelek dalam agama Buddha, artinya memberikan pelayanan kepada umat dengan berlandaskan pada kompetensi dan intelektualitas yang dimiliki. Perilaku keberagamaan yang terbentuk pada umat Buddha merupakan cerminan dari pelaksanaan ajaran Buddha. Pembiasaan yang terbentuk akan memberikan efek pada meningkatnya keyakinan dan moralitas umat Buddha. Perilaku keberagamaan umat Buddha mengacu pada sepuluh cara berbuat baik (dasa puññakiriyavatthu). Pembiasaan pada perilaku yang muncul berdasarkan teladan, dan pengalaman khusus dari para pemimpin, yaitu para dharmaduta.